Flipping Interferometric Module for Simultaneous Dual-Wavelength Unwrapping of Quantitative Phase Maps of Biological Cells - Karako, Lidor; Guo, Rongli; Barnea, Itay; Shaked, Natan T. (Frontiers in Physics, 2021)
We present an imaging platform for stain-free quantitative imaging of biological cells using a simultaneous dual-wavelength holographic module. We use this module to experimentally solve the problem of 2π phase ambiguities that occurs in spatial locations where the optical thickness of the sample is larger than the wavelength. Thus, the process does not require using digital phase unwrapping that is computational heavy and impairs real-time processing. The proposed method is not limited to sequential acquisition of two quantitative phase maps in different times, but rather allows optical multiplexing of two off-axis holograms on the camera at once, enabling acquisition of fast dynamic processes. The module is simple and portable, making it attractive for clinical use. We demonstrate using the module for quantitative phase imaging of cancer and sperm cells.